Improve your marketing and grow your business - Patnaik, Keshu (New Delhi, 2009)
This book provides the tools and techniques to harness the power of modern technologies to succeed in doing business. It presents the shift in thinking that must take place to tap into this new marketing capability, including focusing on becoming customer-centric, reengineering the marketing function, re-thinking the marketing organisation and re-designing the technology systems. This book will definitely help you to build a revolutionary marketing organisation and use it to achieve unprecedented business results.
Keywords: Marketing management